PROMOTER POLYMORPHISM OF IL-1β GENE IN PATIENTS WITH A HISTORY OF ACUTE MYOCARDIAL INFARCTION - A. V. Shevchenko; O. V. Golovanova; V. I. Konenkov; M. I. Voevoda; V. N. Maximov (Медицинская иммунология, 2014)
We have performed analysis of associations between IL-1β gene promoter polymorphism (-511C/T and -31 T/C variants), and conventional cardiovascular risk factors in the patients living in the West Siberia who had previously a history of myocardial infarction (MI). We are shown a strong linkage disequilibrium between IL-1β -31C/T (rs1143627), and IL-1β-511T/C (rs16944). Significant differences in frequency distributions of some compound genotypes were observed between healthy and patients with a history of MI. E.g., frequency of IL-1β-31CC/-511CT genotype was detected in 5.5 % of healthy population, while being absent among MI patients. A frequency of IL-1β (-31/-511) CC/CT genotype showed significant differences between MI patients under 55 years, as compared to healthy persons. Hence, the analyzed IL-1β promoter polymorphisms may be considered as an additional constitutional factor predisposing for vascular alterations.